(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
The banana Dominico Hartón (Musa AAB Simmonds) is of high economic impact in the department of Quindio. Due to lack of studies we carried out the characterization of the plantains during the stage of maturity, harvested to 18 weeks after flowering, the assessment postharvest was after 14 days, doing analysis in triplicate of physicochemical changes of weight, color, index of sweating, index of respiration, firmness, pH, heartburn, water activity and Brix degrees. The results showed weight loses approximately 25%, range of color had variation for example L* from 53.53 to 63.93, for a* from -13.19 to 7.91 and for b* from 34.04 to 49.20, the firmness decreased from 22.78 to 3.41 N/seg, the pH decreased from 5.8 to 4.1, water activity from 0.997 to 0.962 and brix degrees increased from 3.0 to 22.2. The maturation parameters showed climateric characteristics. During maturation is evident the weight loss, color change, decrease in firmness, pH and water activity and an increase in the brix degrees.